Penerapan Model Discovery Learning Pada Mata Pelajaran IPAS untuk Meningkatkan Keaktifan Belajar Siswa Kelas 5 SDN Tangkisan Pos Klaten - Rofisian, Nela; Rahmawati, Isna; Ferryka, Putri Zudhah; Suwartini, Sri (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
Student learning engagement refers to learning activities that directly involve students during the learning process. Student learning engagement is a key determinant of teaching success in schools. The purpose of this study is to improve the learning activity of 5th grade students of SDN Tangkisan Pos Klaten through the Discovery Learning learning model in the subject of Science. This study is motivated by the low learning activity of 5th grade students in the subject of Science, seen from the low learning activity of students at 42.85%. This is because the learning model used is not innovative enough and does not meet students' learning needs, resulting in students being less enthusiastic about participating in class. The type of research used is classroom action research using the Kemmis & McTaggart model. This research model consists of four stages: planning, action implementation, observation, and reflection. The research subjects were all 28 fifth-grade students at SD N Tangkisan Pos. Data collection techniques used observation and documentation. The data analysis technique used was descriptive analysis with percentages. The results of this study indicate an increase in learning activity in each cycle. Student learning activity in cycle 1 averaged 67.85%. In cycle 2, it increased by 17.86%, with an average of 85.71%. These results reveal a significant increase in student learning activity in the science subject through the application of the discovery learning model.